Biruma no tategoto = The Burmese harp [videorecording (DVD)] - Ifukube, Akira, 1914-2006 (Criterion collection, 2007)
"An Imperial Japanese Army regiment surrenders to British forces in Burma at the close of World War II and finds harmony through song. A private, thought to be dead, stumbles upon spiritual enlightenment disguising himself as a Buddhist monk and stumbles upon spiritual enlightenment. Magnificently shot in hushed black and white"--Container.